Peripartum cardiomyopathy and acute pulmonary edema - Razzeto Ríos, Luis (2015)
A 31- year-old woman in the thirty-four week of her second pregnancy was admitted with diffuse sudden-onset abdominal pain. Examination revealed cervical dilation to 7 cm and transverse presentation of the fetus,indications for emergency cesarean section, which was performed uneventfully under spinal anesthesia. Two days after surgery the patient presented signs consistent with acute pulmonary edema. Echocardiography demonstrated left ventricular systolic dysfunction with an ejection fraction of 32%. The diagnosis was peripartum myocardiopathy with acute respiratory insufficiency due to heart failure. Furosemide and captopril were prescribed and the outcome was satisfactory. The discharge echocardiogram showed a left ventricle of normal size and thickness, and the ejection fraction was 50%. Peripartum myocardiopathy is a type of heart failure that develops during the third trimester or during the first six months after delivery, in the absence of signs of ventricular dysfunction or previous heart disease. Based on clinical presentation and echocardiographic findings we believe that peripartum myocardiopathy was the cause of acute pulmonary edema in this patient. We are presenting the first case of peripartum myocardiopathy in Peru.